Bharat Footwear Limited discount coupons - Shah, Bhavin J.; Ravichandran, N. (London : Indian Institute of Management, Ahmedabad, 2018)
The case presents a customer experience while purchase of a pair of shoes in the upmarket retail outlet Bharat Footwear Limited (BFL), in Ahmedabad, India. While negotiating the purchase of the pair of shoes, the customer is offered a 20% discount coupon meant for BFL shareholders, for a split consideration in the ratio of 60 (buyer) and 40 (agent). The customer must decide if they should accept the deal and leads to a discussion as to whether BFL should continue the promotion.
Originally Published In Shah, B. J., & Ravichandran, N. (2018). Bharat Footwear Limited Discount Coupons. QM0282TN. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Marketing -- India -- Ahmadābād -- Decision making -- Case studies; Industrial management -- India -- Ahmadābād -- Case studies; Coupons (Retail trade) -- India -- Ahmadābād -- Case studies